Historical review of land use changes in Portugal (before and after EU integration in 1986) and their implications for land degradation and conservation, with a focus on Centro and Alentejo regions - Jones, Nádia; de Graaff, Jan; Rodrigo, Isabel; Duarte, Filomena (Applied Geography, 2011)
Changes in land use and production systems are to a large extent responsible for land degradation. In Portugal this process has been triggered mainly by socioeconomic drivers, such as agricultural technology, demography and policy changes. In this article land use changes in Portugal are discussed in terms of their main drivers and impacts, focussing on land degradation and conservation. The discussion includes a brief outline of historical land use changes in Portugal and a more detailed account of the changes in the period after 1986, when Portugal joined the European Union. An assessment of recent (1986e2006) land use changes and their impact was conducted for two selected research areas in the Centro and Alentejo regions. This assessment was based on information from the CORINE Land Cover programme (1985 and 2006) and the National Agricultural Census (1989 and 1999). In the Centro research area the land under forest declined from 52% to only 22% of the area, mainly as a result of forest ﬁres. In the Alentejo research area the major change was the decline of miscellaneous shrub, declining from 23% to 11%, to open forest land, increasing as a result of afforestation measures from 1% to 22%. These land use changes resulted in a signiﬁcant increase of soil loss estimates through RUSLE. In the Centro research area soil losses greater than 10 t ha 1 yr 1 were estimated to occur in 57% of the area in 1990, increasing as a result of land use change to 64% in 2006. In the Alentejo research area this change was from 65% in 1990 to 72% in 2006. The research raises questions regarding land use management, in relation to the Common Agriculture Policy support during the 1986e2006 period. Despite the increase in forest and permanent grassland areas, soil loss rates remain very high in the two research areas.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Afforestation; Agri-environmental policy; History; Land degradation; Land-use changes; Portugal

A landscape in transition: an historical perspective on a Spanish latifundist farm - Pérez, A S; Remmers, G G A (Agriculture, ecosystems & environment, 1997)
An agricultural landscape, as a social construction, is not static, but a reflection of the balance of social forces which influence the way in which the natural resources of the site are combined. To understand and evaluate the current configuration of a landscape, and to define and understand criteria according to which a future landscape may be designed, it is necessary to analyse its historical construction. In this paper we follow these steps, taking as a point of reference a farm in one of the most important agricultural regions of Spain, the Guadalquivir river valley in Andalucla. This region stands out for its high production potential, social inequity and environmental degradation. The paper describes global changes in the use of the land in this river valley over the past 3 centuries, and uses aerial photographs from 1956 and 1990 to outline changes on the 1150-ha Los Humosos farm, recently granted to a co-operative of land labourers after years of struggle for land. Through this change in tenure the criteria 'control' and 'distribution of benefits' are achieved. Nine other criteria derived from the historical analysis were used to compare four different farm design scenarios through multi-criteria programming, which was preceded by an assessment of the biogeophysical characteristics of the land. However, this appeared to be insufficient to cope with essential criteria such as landscape architecture and biodiversity, because minor landscape elements were neglected which are important starters for the design of an ecological infrastructure. Water, a problematic resource in Mediterranean agriculture, paradoxically turned out to be an important characteristic of these landscape elements. From historical, ecological and social perspectives, new proposals for farm landscape design must necessarily and radically break with the recent past. It appears, however, that to produce agricultural landscapes of quality in the Guadalquivir river valley would involve tough social struggle, that nonetheless is found to use the margins left over by the dominant socio-economic, cultural and political structures. Finally, an agro-ecological option is proposed as a transitional design
Keywords: ecological agriculture; History; land labourers; landscape; Mediterranean; Spain; water